Studentsâ Experience in Student-Centered Learning at Higher Education Institutions in China: A Case Study - Tsegay, Samson Maekele (EDUCARE, 2015)
ABSTRACT: This paper focuses on studentsâ experience in student-centered learning at Higher Education Institutions (HEIs) in China. Socio-economic transformation and growth in China have led to unprecedented changes in higher education in the past three decades. The notion of world class university is high on the policy agenda at governmental and institutional levels in China. As a result, Chinese higher education has expanded tremendously both in quality and quantity. However, a slow progress has been made in engaging students in the teaching-learning process, both as beneficiaries and implementers. The study found out that studentsâ experiences in student-centered learning at HEIs in China are characterized by different developments and challenges. Despite the different challenges, HEIs students in China are experiencing some benefits of student-centered class environment. The students are able to share ideas and experiences, learn collaboratively, and apply content-based knowledge into real world problems. However, there is still a major problem with regard to recognizing each and every student and embracing them to the class interaction equally. Some students are dominant, while others participate rarely in the class interaction. The interaction of students is highly influenced by the experience and perception of instructors towards studentsâ participation. The facilitation of the instructor can recognize or marginalize students in a class and could greatly affect their participation and building up of a strong student-centered learning environment. This paper contributes in making learning more participatory, enjoyable, and meaningful.KEY WORDS: Student-centered learning, studentsâ experience, pedagogy, higher education institutions in China, share ideas and experiences, learn collaboratively, and apply content-based knowledge.About the Author: Samson Maekele Tsegay was a Program Coordinator at the National Board for Higher Education (NBHE), Eritrea. He is currently pursuing his graduate study in comparative education at the Faculty of Education BNU (Beijing Normal University), 19 Xinjiekouwai Street, Beijing, China 100875. The author can be contacted via phone:Â (+86) 18813044150 or e-mails at:Â samex221@gmail.com and samex221@yahoo.comHow to cite this article? Tsegay, Samson Maekele. (2015). âStudentsâ Experience in Student-Centered Learning at Higher Education Institutions in China: A Case Studyâ in EDUCARE: International Journal for Educational Studies, Vol.7(2) February, pp.135-146. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (November 21, 2014); Revised (December 29, 2014); and Published (February 28, 2015).